Piezoelectric properties of triply periodic minimum surface structures. (10th November 2020) - Xu, Hu; Xie, Yi Min; Chan, Ricky; Zhou, Shiwei
Abstract: Piezoelectric ceramic-polymer composites have attracted substantial interest owing to their distinct piezoelectric performance. This paper investigates the dependence of their output voltage on the volume fraction and structure of the ceramic component, together with the type of stimulus, using finite element analysis. When ceramic parts of piezocomposites are shaped into structures with a topology of triply periodic minimum surface such as Schwarz Primitive surface, Gyroid surface, and Neovius surface, they exhibit much better piezoelectric performance than existing piezocomposites under both the compressive strain and the shear strain. Compared to a piezocomposite with three intersecting ceramic cuboids, Schwarz piezocomposite with the same volume fraction of 50% can increase output voltage by approximately 50% under compressive strains 2%–8%. With 16% ceramic material and under a compressive strain of 8%, Neovius piezocomposite demonstrates ~17-fold and ~6, 000-fold enhancement of output voltage than that of the piezocomposite in the 3-3 mode (connected and irregularly-shaped ceramic component) and in the 0–3 mode (disconnected ceramic particles), respectively. Under simple shear, performance superiority of Neovius piezocomposite to that of the 3-3 mode piezocomposite becomes more significant as output voltage can be enhanced up to approximately 30-fold. Computational analysis shows that high von Mises stress helps to enlarge the difference between positive and negative electrical potential, and therefore enhance output voltage. The findings in this work also reveal output voltage is inversely proportional to strain energy stored in piezocomposites. Because Schwarz piezocomposite has the largest bulk modulus with minimum strain energy under compression, it has the maximum output voltage. Graphical abstract: Image 1